2010
DOI: 10.1111/j.1525-139x.2010.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients Remain on Intensive Hemodialysis Rather than Choosing to Receive a Kidney Transplant?

Abstract: Most dialysis patients would choose to receive a kidney transplant if possible. However, some patients who are receiving intensive hemodialysis (HD) have opted against transplantation and have chosen to remain on dialysis. In this paper, we examine studies that help to inform the decision between receiving a kidney transplant and remaining on intensive HD. There are no randomized trials directly comparing transplant to intensive HD. Database and prospective nonrandomized studies support a number of conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
(26 reference statements)
0
12
0
3
Order By: Relevance
“…Renal transplant is universally preferred over dialysis as a treatment modality because of the enhanced survival and reduced morbidity. However, with the growing interest in and access to more intensive hemodialysis treatments, reports have emerged of patients who opt against transplantation to remain on intensive dialysis . We have previously reported that changing to DHD does not change exercise capacity (as measured by peak oxygen uptake) or the physiologic determinants of exercise capacity, whereas there is a significant improvement in these physiologic measurements with receipt of a kidney transplant .…”
Section: Discussionmentioning
confidence: 98%
“…Renal transplant is universally preferred over dialysis as a treatment modality because of the enhanced survival and reduced morbidity. However, with the growing interest in and access to more intensive hemodialysis treatments, reports have emerged of patients who opt against transplantation to remain on intensive dialysis . We have previously reported that changing to DHD does not change exercise capacity (as measured by peak oxygen uptake) or the physiologic determinants of exercise capacity, whereas there is a significant improvement in these physiologic measurements with receipt of a kidney transplant .…”
Section: Discussionmentioning
confidence: 98%
“…Kidney transplantation (KT) represents the treatment of choice for patients with end-stage renal disease and provides survival benefit when compared with long term dialysis therapy, in terms of quality of life and life expectancy [1], [2]. With the goal of improving transplantation outcomes, donor and recipient selection criteria are evolving.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well-established that post-transplantation occurrences such as DGF and ACR are risk factors for poorer intermediate-term graft survival, increasing the burden of patients returning to dialysis therapy [2], [11], [14], [15]. According to UNOS data, the incidence of DGF is highest with DCD kidneys (44%), intermediate with ECD kidneys (33%), and lowest with SCD kidneys (21%) [2], [11], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Eine Stadienteinteilung der Nierenerkrankungen und chronischen Niereninsuffizienz ausschließlich auf Basis der errechneten glomerulären Filtrationsleistung (eGFR) ist nicht ausreichend. Daher wird diese rein hämodynamische Betrachtungsweise zunehmend durch weitere Parameter ergänzt wie die Proteinurie, Anämie, den sekundären Hyperparathyreoidismus, die arterielle Hypertonie und eventuell vorliegende Begleiterkrankungen [6,7,8]). …”
Section: Langzeitüberleben Bei Chronischer Niereninsuffizienzunclassified